Agriculture and EU Enlargement - Susan Senior Nello (Romanian Journal of European Affairs, 2002)
Agriculture poses considerable tensions for enlargement of the European Union, because of its continuing importance both in the economies of the applicant countries of Central and Eastern Europe, and in the EU budget and acquis communautaire. The preparation of agriculture in the candidate countries to join the EU is rendered more complex by the fact that the Community’s Common Agricultural Policy is a moving target. The aim of this paper is to provide a survey of recent developments relating to food and agriculture in the EU and Central and East European candidate countries in order to indicate the main challenges and difficulties posed by enlargement. It seems likely that agricultural policy in an enlarged EU will attach increased priority to objectives such as food safety, rural development and the environment. However, these new priorities may be expensive to realise, and may impose a growing burden on the national budgets of EU member states.